Archeological Investigations of Portions of the Middle Concho Valley, Texas - Hurt, Richard Dwain (Texas Tech University, 1980)
An archeological survey of portions of the Middle Concho River in western Tom Green and eastern Irion Counties of Texas was the basis for this study. In addition to first conducting a field survey, it was deemed necessary to determine chronological and cultural indicators to establish the age of occupation for the area. It was further necessary to relate these temporal occupations to site placement and density based on topographic variation for the area. The data reflect the exploitation potential of important resources and how these resources would change through time. Forty-eight sites were discovered in various topographic regions. These sites were generally open encampments with large quantities of chipped stone and fire-fractured limestone. Based on diagnostic artifacts (projectile points) a chronological sequence for the area was established with a time range spanning a period of 6-7000 years. As viewed in the archeological dates a slight decline in the frequency of usage of the area occurs during the Middle Archaic and perhaps into the early part of the Late Archaic. This is viewed as a direct result of the decline of bison and perhaps other game animals on the southern plains. During the Late Archaic area occupation reached its peak bringing with it evidence of a new ethnic group with affiliations belonging to the Central Texas area. Prior to 1000 B.C. projectile point types and cultural affiliations appear to have been associated with Trans-Pecos complexes of southwest Texas.